Assessing the moderating role of ESG performance on corporate governance and firm value in developing countries - Ayishetu Bukari; Andrew Osei Agyemang; Bernard Bawuah (Cogent Business & Management, 2024)
This study investigates the effects of corporate governance (CG) attributes on firm value (FV), considering the moderating effect of ESG performance. This study considers the three strands of corporate governance, thus board's structural, diversity and process attributes, which have not been considered in prior studies. The study employed the Common Correlated Effects Mean Group (CCEMG) and the Augmented Mean Group (AMG) for the empirical analysis. The study utilized a quantitative research methodology sourcing data from 362 manufacturing companies from Sub-Saharan Africa from 2010 to 2022. The findings indicate that regarding board diversity attributes, both gender diversity and the presence of foreign nationals exhibit positive associations with FV. Regarding board structural attributes, independent boards and board size also influenced FV positively. However, CEO duality shows a negative assosciation with FV. Regarding the process attributes, holding regular board meetings enhances FV, while low meeting attendance negatively affects FV. Moreover, the study also evidenced that ESG performance exerts a substantial positive impact on the link between CG and FV. The findings underscore the need for policymakers to enact stringent regulations compelling firms to integrate ESG principles into their governance structures, as it enhances firm value.
Keywords: 650; corporate governance; firm value; ESG performance; manufacturing companies; developing countries